2014
DOI: 10.2500/aap.2014.35.3770
|View full text |Cite
|
Sign up to set email alerts
|

Comparative safety and efficacy of two formulations of mometasone nasal spray in adult seasonal allergic rhinitis

Abstract: Mometasone furoate as a nasal spray is an effective treatment for seasonal allergic rhinitis (SAR). An aqueous mometasone nasal spray containing the same active substance and excipients as the originator product (reference mometasone) has been developed. This study was designed to establish therapeutic equivalence of test mometasone to reference mometasone and superiority over placebo for the treatment of SAR in adults. In this multicenter, randomized, double-blind, placebo- and active-controlled, fixed-dose s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…22-36 The risk ratio for patients treated with mometasone furoate was 1.48 (95% CI, 1.06-2.07; I 2 = 3%; Figure 6 ). 37-50 Fluticasone propionate was associated with an intermediate risk ratio of 1.36 (95% CI, 1.00-1.85; I 2 = 0%; Figure 7 ). 17,48,51-65…”
Section: Resultsmentioning
confidence: 99%
“…22-36 The risk ratio for patients treated with mometasone furoate was 1.48 (95% CI, 1.06-2.07; I 2 = 3%; Figure 6 ). 37-50 Fluticasone propionate was associated with an intermediate risk ratio of 1.36 (95% CI, 1.00-1.85; I 2 = 0%; Figure 7 ). 17,48,51-65…”
Section: Resultsmentioning
confidence: 99%
“…Following published procedures 23 with modifications, the medication scores were recorded for each patient during the period of treatment. When necessary, the patients were allowed to take anti-histamine tablets (levocetirizine; 5 mg/tablet) or/and nasal spray of corticosteroid (mometasone).…”
Section: Methodsmentioning
confidence: 99%
“…The number of side-effects associated with usage of intranasal glucocorticosteroids was comparable to placebo [15]. In a multicenter, randomized, double-blinded clinical trial Kuna et al indicated the equivalence of two mometasone preparations (original and generic) in effective reducing of nasal and ocular symptoms of allergic rhinitis, with good tolerance and without any serious side-effects [16].…”
Section: Intranasal Administration Of Glucocorticosteroidsmentioning
confidence: 99%